Quality of educational dialogue and association with students' academic performance. (June 2018) - Muhonen, Heli; Pakarinen, Eija; Poikkeus, Anna-Maija; Lerkkanen, Marja-Kristiina; Rasku-Puttonen, Helena
Abstract: The study used a mixed-methods approach to examine the associations between the quality of educational dialogue and students' academic performance and to analyse what kinds of dialogic teaching patterns of different levels of quality can be identified in classroom lessons. A total of 158 Grade 6 lessons were video-recorded, and the quality of the educational dialogue was assessed using the Classroom Assessment Scoring System-Secondary (CLASS-S) observational instrument. Multilevel modelling indicated that the quality of educational dialogue was positively associated with students' academic performance (grades) in language arts and physics/chemistry. Qualitative analysis was subsequently used to examine the quality of the patterns of dialogic teaching in language arts and physics/chemistry lessons (n = 11). The analysis revealed that teacher-initiated patterns were predominant in both subjects and that physics/chemistry lessons were more typically characterised by high-quality educational dialogue than language arts lessons. Highlights: The quality of educational dialogue and students' grades in Grade 6 were examined. The quality of educational dialogue was associated with students' performance. The association was found in language arts and physics/chemistry. Teacher-initiated dialogue dominated language arts and physics/chemistry lessons. The quality of dialogic teaching patterns varied within the two subjects.